Replacement of loop residues in TBA by an abasic ethylene glycol spacer: effect on stability, structure and function** - Wagh, Atish A.; Ghalawat, Monika; Fernandes, Moneesha (ChemistrySelect, 2021)
This article describes the synthesis of ethyleneglycol (E) phosphoramidite and its incorporation into the thrombin binding aptamer (TBA) sequence at loop positions. Circular dichroism (CD) study revealed no major disturbances in the secondary structure of TBA by the abasic E unit and the derived oligomers exhibited a typical antiparallel chair-like conformation similar to that of TBA. UV and CD spectroscopy, together with anti-coagulation and HPLC studies revealed that although nuclease stability was enhanced, and anti-coagulation reasonably good, the thermal stability of the quadruplexes was adversely affected.
Keywords: aptamers; clotting time; ethylene glycol spacer; G-quadruplexes; nuclease stability